The grammar of messianism: an ancient Jewish political idiom and its users - Novenson, Matthew V. (Oxford University Press, 2017)
1. After the Messianic Idea -- 2. Oil and power in ancient Israel -- 3. Messiahs born and made -- 4. Messiahs present and absent -- 5. The quest for the first Messiah -- 6. The Jewish Messiah-Christian Messiah distinction -- 7. The fate of Messiah Christology in early Christianity -- 8. The grammar of Messianism